Regional comparisons of the accessibility and use of ICT in the regions of Russia: the possibility of using integrated indicators - S. G. Bychkova; L. S. Parshintseva (Статистика и экономика, 2020)
The aim of the study. The aim of the study is a statistical analysis of the accessibility and the use of information and communication technologies for the population and households based on the developed integrated indices in the regional aspect.Fundamental international documents refer to the increasing role of information in all spheres of society, and indicate that the number of the poorest households with, for example, a mobile phone is higher than that with the access to clean drinking water.Thus, it can be noted that the level of accessibility and use of information and communication technologies is a priority for the development of both individual countries and the world community as a whole.Materials and methods. Methods of grouping and multidimensional classification, analysis of variation, normalizing, construction of multidimensional averages and correlation analysis, as well as tabular and graphical methods of visual representation of the results of the study were used as statistical tools for the study. Microsoft Excel was used to process the primary information.Results. Comparison of currently used indicators has revealed the need to develop and build integrated indices in four main areas of ICT research: infrastructure (physical and information), ICT accessibility (physical and price affordability), the use of ICT (by the population and households, enterprises and organizations, in the public sector), knowledge and skills (education, digital skills). In this study, the analysis was carried out according to the characteristics of the accessibility and the use of ICT for the population and households. The results of the study at the federal district level led to the conclusion that, despite the existence of a unified policy in the field of ICT development and information society at the federal level, there are significant differences in the management of this process and the level of implementation of system development measures for ICT in individual federal districts and regions. The main result of the study is the classification of regions by levels of accessibility and use of ICT. The analysis revealed a significant direct relationship between the components of ICT accessibility and its use. The ratings based on the calculated multidimensional averages allowed us to reveal the leader and lagging regions of the Russian Federation in terms of the development of ICT and information society.Conclusion. According to the results of the statistical research positions of regions of the Russian Federation on the accessibility levels and the use of information and communication technologies were determined, as well as a direct relationship between the indices of accessibility and the use of ICT was revealed as a whole in the Russian Federation, and in individual federal districts.